Parallel Affine Immersions ${M^n}→ {{\mathbb{R}}^{n+2 }}$ with Flat Connection - Shugailo, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We present a classification of parallel affine immersions $f : M^n→{M^n}→ {{\mathbb{R}}^{n+2 }}$ with flat connection according to the rank of the Weingarten mapping.